2016
DOI: 10.1016/j.jcrs.2015.11.039
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the Barrett True-K formula for intraocular lens power prediction after laser in situ keratomileusis or photorefractive keratectomy for myopia

Abstract: The Barrett True-K formula was either equal to or better than alternative methods available on the ASCRS online calculator for predicting IOL power in eyes with previous myopic LASIK or PRK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
118
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(133 citation statements)
references
References 20 publications
10
118
1
4
Order By: Relevance
“…With a similar population, Alfonso et al noted that 27% of eyes were >0.50D away from the target refraction; these eyes also had previous hyperopic LASIK and were implanted with the ReSTOR SN60D3 lens (Alcon Laboratories, Inc.). 12 Of note also is that Abulafia et al 5 who used the Barrett True-K formula in patients with previous myopic LASIK or photorefractive keratectomy noted that 67% were within AE0.50D from target refraction while 91% of eyes in the current study were within AE0.50D from target. Results in the current study are also better than reported in other studies using other calculation methods where the highest reported percent of eyes within AE0.5D was 84%.…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…With a similar population, Alfonso et al noted that 27% of eyes were >0.50D away from the target refraction; these eyes also had previous hyperopic LASIK and were implanted with the ReSTOR SN60D3 lens (Alcon Laboratories, Inc.). 12 Of note also is that Abulafia et al 5 who used the Barrett True-K formula in patients with previous myopic LASIK or photorefractive keratectomy noted that 67% were within AE0.50D from target refraction while 91% of eyes in the current study were within AE0.50D from target. Results in the current study are also better than reported in other studies using other calculation methods where the highest reported percent of eyes within AE0.5D was 84%.…”
Section: Discussionsupporting
confidence: 42%
“…noted that 27% of eyes were >0.50D away from the target refraction; these eyes also had previous hyperopic LASIK and were implanted with the ReSTOR SN60D3 lens (Alcon Laboratories, Inc.) . Of note also is that Abulafia et al . who used the Barrett True‐K formula in patients with previous myopic LASIK or photorefractive keratectomy noted that 67% were within ±0.50D from target refraction while 91% of eyes in the current study were within ±0.50D from target.…”
Section: Discussionmentioning
confidence: 46%
“…This relatively simple regression formula, originally developed for eyes with prior laser refractive photoablation, modifies the predicted IOL power by taking into account the surgically induced refractive change at the corneal plane 3 . The unpublished Barrett True K formula can be used with or without considering the surgically induced refractive change because it employs an internal regression formula to estimate the surgically induced change in manifest refraction when those data are unavailable 13 . Interestingly, in this sample of post-SMILE eyes, the accuracy of the Barrett True K formula was not clinically significantly deteriorated when preoperative refractive data were not entered but estimated (Barrett True K No History formula).…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [13] evaluated various IOL formulas from the American Society of Cataract and Refractive Society post-LASIK IOL calculator [24] and showed that formulas using no prior data and refractive change after LASIK were more accurate than the clinical history method. Abulafia et al [34] found that the Barrett True K No History formula had significantly smaller variance in prediction error than the Shammas formula and performed similar to the Haigis-L and Modified-Masket formulas. A meta-analysis by Chen et al [35] concluded that the clinical history method was significantly inaccurate in predicting postoperative refraction than the Haigis-L formula.…”
Section: Discussionmentioning
confidence: 99%